EFFECT OF CUSTOMER EXPECTATIONS AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT PT. INDOMETRO SURYA ANDOLA IN METRO CITY - Bambang Satriawan; Davis Aryadi (Derivatif : Jurnal Manajemen, 2019)
The effort that must be done by the company in order to be successful in competition is to try to attract the interest of customers. The factor that is often a concern is customer expectations and product quality in providing services to customers which is a measure of customer satisfaction. The purpose of this study was to determine the effect of customer expectations and product quality on customer satisfaction at PT. Indometro in Metro City.The method used in this study is an explanatory survey method. This type of research is quantitative research with the object of research is customer expectations, product quality and customer satisfaction. The research population is PT. Indometro Unit II Metro City with a total sample of 96 respondents. Data collection techniques using interviews, documentation and questionnaires using questionnaires. The analytical tool used is using data quality analysis and multiple linear regressionanalysis.The results showed that customer expectations had a significant effect on customer satisfaction, product quality had an effect on customer satisfaction. And simultaneously customer expectations and product quality together have a positive effect on customer satisfaction. Looking at these results it can be said that independent variables have a positive and significant effect on customer satisfaction. Keywords: Customer expectations, product quality, customer satisfaction